Aplikasi Model QUAL2Kw dalam Penilaian Kualitas Air Sungai Kambang Parameter BOD dan NH3-N - Nuzul Hafiizha Asyari; Siti Umi Kalsum; Marhadi Marhadi (Universitas Batanghari Jambi, 2026)
The Kambang River is a river in Jambi City that passes through densely populated residential areas and shopping centers, making it vulnerable to pollution from both point and non-point sources. This study aims to model the water quality of the Kambang River using QUAL2Kw software on the Biochemical Oxygen Demand (BOD) and Ammonia as nitrogen (NH3-N) parameters in response to increasing discharge and pollutant levels from point sources. Sampling was conducted using grab sampling at nine points representing the upstream, midstream, and downstream segments. The test results were compared with the river water quality standards and similar waters, Class II, Appendix VI of Government Regulation No. 22 of 2021 concerning the Implementation of Environmental Protection and Management. River hydraulic data (discharge, width, depth, flow velocity, and riverbed slope) were used as input data in the QUAL2Kw worksheet. Data calibration was performed using trial and error, then data validation using the Root Mean Square Percentage Error (RMSPE) method. The results of water quality testing showed that the BOD and NH3-N parameters at all sampling points did not meet the established quality standards. The BOD test value ranged from 7.10 to 16.20 mg/L with a quality standard of 3.00 mg/L, and the NH3-N test results ranged from 3.03 to 14.13 mg/L with a quality standard of 0.20 mg/L. The model validation results using the RSMPE method for discharge parameters were 3.21%, BOD 3.88%, and NH3-N 0.46%, meeting the criteria of